Kinetic properties of Rhizopus oryzae RPG1 endo-polygalacturonase hydrolyzing galacturonic acid oligomers. (January 2016) - Mertens, Jeffrey A.; Bowman, Michael J.
Abstract: The kinetic characteristics of Rhizopus oryzae endo-polygalacturonase, RPG1, hydrolyzing galacturonic acid oligomers (Gal p A) n were determined. RPG1 generates (Gal p A)3 as a dominant product of polygalacturonic acid and (Gal p A)4–6 hydrolysis. The enzyme can hydrolyze (Gal p A)3, but hydrolysis occurs at a significantly lower rate relative to oligomers with a higher degree of polymerization. Hydrolysis of the α-1, 4 glycosidic bond by RPG1 is an endothermic process with a Δ H app, of 1.03±0.04 kcal/mol. Determination of kinetic constants by isothermal titration calorimetry showed that for oligomers (Gal p A)3–6, the K m decreased and the k cat increased as the length of the (Gal p A) oligomer increased. Fixed time point assays followed by chromatographic analysis provided apparent k cat values similar to those found using isothermal titration calorimetry. Assays to determine to what extent the enzyme is subject to product inhibition demonstrated that the enzyme is competitively inhibited by (Gal p A)2 when using (Gal p A)4 as substrate. The apparent K i of 767 μM is significantly higher than the K m values obtained for the series of galacturonic acid oligomers.